Analysis of Nutritional Status in Adolescent Girls at PGRI 1 Senior High School, Bogor City - Resti Aananda; Rukmaini; Rini Kundaryati (Rajaki of Tulip Medika Publisher, 2025)
Adolescents are an age group experiencing accelerated physical growth and psychosocial development, thus having high nutritional needs. Imbalanced nutritional intake can cause problems such as anemia, obesity, or malnutrition. At SMA PGRI 1 Bogor City, the prevalence of nutritional problems in adolescents is still quite high. To analyze factors related to nutritional status in adolescents at SMA PGRI 1 Bogor City in 2025. This study used a quantitative approach with a cross-sectional design . Data collection was carried out through questionnaires and anthropometric measurements (BMI). The variables studied included body image, physical activity, nutritional knowledge, dietary patterns, family support, consumption of Fe tablets, and stress levels. Data analysis was carried out using Spearman's bivariate statistical test . There is a significant relationship between nutritional status and nutritional knowledge (p=0.001; r=0.879), body image (p=0.001; r=0.897), eating patterns (p=0.001; r=0.810), physical activity (p=0.001; r=0.818), family support (p=0.001; r=0.780), consumption of Fe tablets (p=0.001; r=0.726), and stress levels (p=0.001; r=0.850). There is a significant relationship between body image, physical activity, nutritional knowledge, eating patterns, family roles, compliance with Fe tablet consumption, and stress levels with the nutritional status of adolescent girls. Nutrition education interventions and the formation of healthy living habits in schools are needed, as well as family involvement in supporting the fulfillment of balanced nutrition for adolescent girls.